2006
DOI: 10.1590/s0004-282x2006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic state in rats submitted to status epilepticus during development

Abstract: -The effect of glycemic state on status epilepticus (SE) development was studied in animals of d i ff e rent ages, submitted to pilocarpine model of epilepsy. Groups: I-Rats with 9-day-old (P9): IA. Submitted to 1SE; IB. Saline-treated; IC. Induced-hyperglycemia; ID. Induced-hyperglycemia+SE; II-Rats submitted to t h ree consecutive episodes of SE at P7, P8 and P9; III-Rats submitted to 1SE at P17; IV-Rats submitted to 1SE at P21. Hippocampal cell death and the expression of glucose transporter GLUT3 were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(4 reference statements)
0
4
1
Order By: Relevance
“…There existed observations suggesting that hyperglycemia only does not necessarily augment neuronal damage in SE (Swan et al 1986;Santiago et al 2006). Compared to our studies, these different results might be due to a single glucose infusion, a relatively small number, a different SE-induced model and age (the developing rats, not the adults).…”
Section: Discussioncontrasting
confidence: 97%
“…There existed observations suggesting that hyperglycemia only does not necessarily augment neuronal damage in SE (Swan et al 1986;Santiago et al 2006). Compared to our studies, these different results might be due to a single glucose infusion, a relatively small number, a different SE-induced model and age (the developing rats, not the adults).…”
Section: Discussioncontrasting
confidence: 97%
“…However, overexpression of GLUT3 will transport too much glucose into the brain and perturb glucose metabolic homeostasis. Some reports suggested that hyperglycemia could enhance hippocampal GLUT3 mRNA and protein expression to enhance glucose uptake and damage the brain function (Reagan et al, 2000;Santiago et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In neurodegenerative disorders, a neuroprotective effect of the KD is mediated by the ability of neurons to afford a very high metabolic level (Gasior et al., 2006; Maalouf et al., 2007). The lithium‐pilocarpine SE induces neuronal loss in highly metabolic challenged structures like the hippocampal complex and the parahippocampal cortices (Turski et al., 1983, 1989; Cavalheiro, 1995; Dube et al., 2000b, 2001; Santiago et al., 2006). In these extreme conditions, glucose oxidative potential is unable to support the acute and sustained metabolic demand that could be partly fulfilled by the alternative energetic pathway provided by the ketone bodies.…”
Section: Discussionmentioning
confidence: 99%